Effectiveness of a hybrid digital substance abuse prevention approach combining e-Learning and in-person class sessions - Griffin, Kenneth W.; Williams, Christopher; Botvin, Caroline M.; Sousa, Sandra; Botvin, Gilbert J. (Frontiers in Digital Health, 2022)
Background: Effective school-based programs for preventing substance abuse offer considerable public health potential. Yet limited class time and uneven implementation fidelity can be barriers to widespread adoption and high-quality implementation. A hybrid digital approach may be effective and help address these barriers. Objective: To evaluate the effectiveness of a hybrid substance abuse prevention program for middle school students consisting of e-learning modules and in-person class sessions. Design: Twenty-three U.S. middle schools were randomly assigned either to an intervention condition (13 schools) or a treatment-as-usual control condition (10 schools) where standard health education material was delivered. Intervention: The hybrid digital intervention consisted of 14 e-learning modules and six classroom sessions adapted from an evidence-based program designed for classroom implementation to increase knowledge of adverse consequences of substance use and improve social skills, personal-coping skills, and skills for resisting social influences to smoke, drink, or use drugs. Measures: Participating students completed online pretest and posttest surveys to assess substance use, knowledge, and life skills. Results: There were significant reductions in cigarette smoking, alcohol use, drunkenness, marijuana use, and the misuse of prescription drugs for the hybrid digital condition compared to the control condition as well as significant increases in health knowledge, skills knowledge, and life skills. Conclusions: A hybrid digital approach to substance abuse prevention is effective and offers potential for overcoming common barriers to widespread adoption and high-quality implementation.